2024
DOI: 10.1039/d3sc05589b
|View full text |Cite
|
Sign up to set email alerts
|

NiH-catalyzed C–N bond formation: insights and advancements in hydroamination of unsaturated hydrocarbons

Changseok Lee,
Hyung-Joon Kang,
Sungwoo Hong

Abstract: This review highlights recent progress in NiH-catalyzed hydroamination, focusing on its application to a variety of alkenes and alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…According to the above results and literature, a plausible reaction mechanism was proposed (Figure c). The nickel­(I) hydride species I , generated from SKP-bound Ni precursor with a silane in the presence of a base, , would insert into the terminal double bond of the 1,3-diene, generating the corresponding π-allyl-Ni­(I) intermediate II .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…According to the above results and literature, a plausible reaction mechanism was proposed (Figure c). The nickel­(I) hydride species I , generated from SKP-bound Ni precursor with a silane in the presence of a base, , would insert into the terminal double bond of the 1,3-diene, generating the corresponding π-allyl-Ni­(I) intermediate II .…”
Section: Resultsmentioning
confidence: 54%
“…Recently, metal hydride-catalyzed hydrofunctionalization of alkenes has attracted considerable attention. It has been reported that some NiH complexes demonstrate robust catalytic activity for enantioselective C–N bond-forming processes, wherein O-benzoyl hydroxylamines (BzO–NR 2 ) are used as electrophilic amination reagent which is compatible to the presence of reductant reagents in the reaction system . Accordingly, we commenced our studies on the Ni-catalyzed model reaction of phenylbutadiene 1a and morpholino benzoate 2a , and a preliminary parameter survey revealed that the reaction was best run at rt in 2-Me-THF with Ni­(COD) 2 as the Ni source in the presence of trimethoxysilane and K 2 CO 3 (for details, see SI).…”
Section: Resultsmentioning
confidence: 99%
“…Palladium catalysis using alkynoates shows a similar reactivity to promote Cα–H bond formation through hydropalladation. 17 b ,19,20 Even though an analogous tendency was observed in our nickel catalysis, the above experimental results are not enough to understand and explain the origin of the regio- and stereoselectivity. Therefore, DFT calculations were performed to investigate the reaction details that control the regio- and stereoselectivity observed in the hydrocyanation of alkynoates.…”
mentioning
confidence: 68%
“…Particularly challenging is the hydrometalation of unactivated internal alkenes, which proceeds much slower than in terminal olefin substrates, often leading to undesirable chain-walking isomerization toward terminal olefins. Consequently, the regio- and enantioselective hydrofluorination of internal unactivated alkenes remains a largely unexplored and challenging area in this field, indicating a significant gap in catalytic methodologies in synthetic chemistry. Our group has dedicated substantial efforts in the successful implementation of NiH catalysis for the transformation of alkenes, utilizing a native carbonyl directing strategy to adeptly maneuver through the intricacies of this field (Figure c). Motivated by this approach, our hypothesis has centered on the efficacy of employing native directing groups in conjunction with an umpolung approach to fluoride in fostering highly regioselective C–F bond formation in diverse olefin structures.…”
Section: Introductionmentioning
confidence: 99%